Effect of ethanol and plant growth regulators on termination of potato microtuber dormancy - Wróbel, Sławomir; Kęsy, Jacek; Treder, Krzysztof (Plant Breeding and Seed Science, 2015)
The duration of dormancy varies significantly among cultivars, but even short dormancy can limit usage of potato microtubers for seed production. The aim of the research was to test efficacy of dormancy breaking by treatment with an aqueous solution of ethyl alcohol, saccharose, gibberellic acid and kinetin (ethanol treatment) in comparison to treatment with aqueous solution of thiourea, daminozide and gibberellic acid (standard treatment). Prolonging the period of microtuber production at the in vitro stage significantly favored the shortening of the dormancy and facilitated its breaking. While the standard treatment had the strongest effect, the ethanol treatment was slightly less efficient. The statistically significant differences were only observed during the first 13 days after the microtuber treatment. After that time, efficacy of ethanol and standard treatments was similar to control treatment with water. The investigated treatments had no effect on the natural decrease of ABA level in microtubers.